Reciclagem e resíduos sólidos no município de São Luís, Maranhão: implicações no contexto saúde e ambiente - Lima, Dyego Bruno Sena (2013)
The research objective was to evaluate the situation of solid waste recycling in São Luís, Maranhão, from January 2009 to December 2011. Therefore, we carried out a survey of information from the organs of the state and municipal levels. Quantitative and qualitative data of recyclable materials marketed as well as their market values were provided by the Secretaria de Estado de Meio Ambiente e Recursos Naturais SEMA (State Department of Environment and Natural Resources SEMA) and the Secretaria Municipal de Meio Ambiente - SEMMAM (Municipal Environment SEMMAM). Additional data were obtained from the Associação de Catadores de Materiais Recicláveis ASCAMAR (Association of Recyclable Materials ASCAMAR) and Cooperativa de Recicladores de São Luís - COOPRESL (Recyclers Cooperative of São Luís COOPRESL), in consultation with their virtual files. Qualitative and quantitative data of solid waste to landfill Municipal of Ribeira were acquired by the Secretaria Municipal de Obras e Serviços Públicos - SEMOSP (Municipal Public Works and Services SEMOSP), manager of the landfill, in consultation with their virtual portal. There was found a total of 671,112kg materials collected by two cooperatives. The cardboard stood out as the main material traded between recyclables (70.%). As for materials destined for landfill Municipal of Ribeira, a greater amount of organic waste (47.%). Found 16 points of open dumps. Market values of recyclable vary from R$ 0.13 / kg to R$ 2.20 / kg, these prices below the national average. In this context, it is known that the recycling market, as well as socioeconomic status and work of recyclers lack of incentives and policies that promote the proper functioning of the recycling process in São Luís, so that the inadequate provision does not jeopardize the public health and welfare of the population.